Unilateral pheochromocytoma in canine female: case report - Mattioni, Laura (Pubvet, 2020)
Pheochromocytoma is a rare neoplasm of chromaffin cells, located in the adrenals which are important for having the ability to incite potentially fatal hypertensive crises. The clinical signs are related to the release of catecholamines. Surgical resection is the definitive treatment, but the clinical treatment also proves useful. The objective was to describe a case of pheochromocytoma in a nine-year-old female dog, who had cutaneous and periocular hematomas, apathetic behavior, anorexia for four days, and polydipsia. The patient was received at the Veterinary Hospital of UNIJUÍ, and after clinical consultation and hospitalization, the tutor opted for euthanasia and necropsy motivated by the dog’s low adherence to treatment. The animal was sent to the Veterinary Pathology laboratory of the same institution that evidenced the right adrenal gland with a proliferation of vacuolated cells focally extensive, concerning pheochromocytoma. Therefore, the veterinarian must know and consider this type of neoplasia.